ALLERGY TESTING METHODS AND THEIR CLINICAL SIGNIFICANCE IN ALLERGIC DISEASES - M.Abdullayeva (Prospects for innovative technologies in science and education, 2026)
Allergic diseases are widespread immunological disorders caused by hypersensitivity reactions to environmental and biological allergens. Accurate identification of the causative allergen is essential for effective management and prevention of allergic reactions. Allergy testing plays a crucial role in diagnosing allergic diseases, guiding treatment strategies, and improving patient outcomes. This article reviews the main methods of allergy testing and highlights their clinical significance.